2015
DOI: 10.1371/journal.pgen.1005571
|View full text |Cite
|
Sign up to set email alerts
|

The Ty1 Retrotransposon Restriction Factor p22 Targets Gag

Abstract: A novel form of copy number control (CNC) helps maintain a low number of Ty1 retrovirus-like transposons in the Saccharomyces genome. Ty1 produces an alternative transcript that encodes p22, a trans-dominant negative inhibitor of Ty1 retrotransposition whose sequence is identical to the C-terminal half of Gag. The level of p22 increases with copy number and inhibits normal Ty1 virus-like particle (VLP) assembly and maturation through interactions with full length Gag. A forward genetic screen for CNC-resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
74
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 33 publications
(82 citation statements)
references
References 95 publications
7
74
1
Order By: Relevance
“…Our results show that p22/p18 inhibits several steps in the process of retrotransposition prior to reverse transcription (Nishida, et al 2015, Saha, et al 2015, Tucker, et al 2015), which clarifies and greatly extends earlier work (Garfinkel, et al 2003, Matsuda and Garfinkel 2009) (Fig. 3).…”
Section: Mechanism Of Restrictionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results show that p22/p18 inhibits several steps in the process of retrotransposition prior to reverse transcription (Nishida, et al 2015, Saha, et al 2015, Tucker, et al 2015), which clarifies and greatly extends earlier work (Garfinkel, et al 2003, Matsuda and Garfinkel 2009) (Fig. 3).…”
Section: Mechanism Of Restrictionsupporting
confidence: 91%
“…The relative amount of p18 verses p22 is correlated with the level of PR produced from Ty1 (Tucker, et al 2015). When PR is expressed from the full ensemble of elements present in a genome or from pGTy1 induction p18 is the predominant form, whereas in low copy strains or an spt3 mutant only p22 is detected.…”
Section: Synthesis Of P22/p18mentioning
confidence: 99%
See 1 more Smart Citation
“…14 A recent study from the Garfinkel lab found that mutations in GAG confer resistance to the p22 restriction factor. 24 Most of the mutations mapped within the Gag region important for VLP assembly but they did not interfere with p22 binding to Gag. 24 Thus, productive Gag/Ty1 RNA interactions were rescued from p22 restriction in those mutants.…”
mentioning
confidence: 96%
“…24 Most of the mutations mapped within the Gag region important for VLP assembly but they did not interfere with p22 binding to Gag. 24 Thus, productive Gag/Ty1 RNA interactions were rescued from p22 restriction in those mutants. Other characterized resistant mutants contained substitutions in the NAC region important for RNA binding but their NAC functions remain to be studied.…”
mentioning
confidence: 96%